Retinal pigment epithelium cell density and Bruch’s membrane thickness in secondary versus primary high myopia and emmetropia - Jonas, Jost B.; Dong, Li; Holbach, Leonard; Panda-Jonas, Songhomitra (Scientific reports, 2020)
To assess differences between secondary high myopia (SHM) due to congenital glaucoma and primary high myopia (PHM) and non-highly myopic eyes (NHM) in the relationships between axial length and Bruch’s membrane (BM) thickness and retinal pigment epithelium (RPE) density. The histomorphometric study included human globes enucleated for reasons such as malignant uveal melanoma, end-stage painful secondary angle-closure glaucoma and congenital glaucoma. BM thickness and RPE cell density were measured upon light microscopy. The investigation included 122 eyes (mean axial length: 26.7 ± 3.7 mm; range: 20.0-37.0 mm): 7 eyes with SHM (axial length: 33.7 ± 2.1 mm; range: 31.0-37.0 mm), 56 eyes with PHM (mean axial length: 29.1 ± 2.4 mm; range: 26.0-36.0 mm) and 59 eyes in the NHM-group (axial length: 23.5 ± 1.3 mm; range: 20.0-25.5 mm). In the SHM group, longer axial length was associated with lower RPE cell density at the posterior pole (standardized regression coefficient beta: 0.92; non- standardized regression coefficient B: −2.76; 95% confidence interval (CI): −4.41, −1.10;P = 0.01), at the midpoint posterior pole/equator (beta: −0.87; B: −3.60; 95% CI: −6.48, −0.73;P = 0.03), and at the equator (beta: −0.88; B: −0.95; 95% CI: −1.68, −0.23; P = 0.02), but not at the ora serrata (P = 0.88). In the PHM-group and NHM group, RPE cell density at the posterior pole (P = 0.08) and ora serrata (P = 0.88) was statistically independent of axial length, while at the midpoint posterior pole/equator (P = 0.01) and equator (P < 0.001), RPE cell density decreased with longer axis. BM thickness in the SHM group decreased with longer axial length at the posterior pole (beta: −0.93;B: −0.29; 95% CI: −0.39, −0.14; P = 0.003), midpoint posterior pole/equator (beta: −0.79; B: −0.22; 95% CI: −0.42, −0.02; P = 0.035) and equator (beta: −0.84; B: −0.21; 95% CI: −0.37, −0.06; P = 0.017), while in the PHM-group and NHM-group, BM thickness at any ocular region was not statistically significantly correlated with axial length (all P > 0.05). In the SHM-group, but not in the PHM-group or NHM-group (P = 0.98), lower BM thickness was associated with lower RPE cell density (beta: 0.93; B: 0.09; 95% CI: 0.04, 0.14; P = 0.007), while in the eyes without congenital glaucoma the relationship was not statistically significant. In SHM in contrast to PHM, BM thickness and RPE cell density decrease in a parallel manner with longer axial length. The findings fit with the notion of BM being a primary driver in the process of axial elongation in PHM as compared to SHM.
Gesehen am 13.10.2020